Time of day differences in the regulation of glutathione levels in the rat lens - Li, Bo; Suzuki-Kerr, Haruna; Martis, Renita M.; Lim, Christopher J. J.; Wang, Zhou-ai; Nguyen, Tai X.; Donaldson, Paul J.; Poulsen, Raewyn C.; Lim, Julie C. (Frontiers in Ophthalmology, 2024)
IntroductionEvidence in non-ocular tissues indicate that the antioxidant glutathione (GSH) may be regulated in a circadian manner leading to the idea that GSH levels in the lens may also be controlled in a circadian manner to anticipate periods of oxidative stress.MethodsMale rat Wistar lenses (6 weeks) were collected every 4 hours over a 24-hour period at 6am, 10am, 2pm, 6pm, 10pm and 2am and quantitative-PCR, western blotting and immunohistochemistry performed to examine the expression of core clock genes and proteins (BMAL1, CLOCK, CRY1-2, PER 1-3) and their subcellular localisation over a 24-hour period. Western blotting of lenses was also performed to examine the expression of NRF2, a transcription factor involved in regulating genes involved in GSH homeostasis and GSH related enzymes (GCLC, GS and GR) over the 24-hour period. Finally, HLPC was used to measure GSH levels in the aqueous humour and lenses every 4 hours over a 24-hour period.ResultsThe rat lens contains the core molecular components of a circadian clock with the expression of core clock proteins, NRF2 and GSH related enzymes fluctuating over a 24-hour period. BMAL1 expression was highest during the day, with BMAL1 localised to the nuclei at 10am. NRF2 expression remained constant over the 24-hour period, although appeared to move in and out of the nuclei every 4 hours. GSH related enzyme expression tended to peak at the start of night which correlated with high levels of GSH in the lens and lower levels of GSH in the aqueous humour.ConclusionThe lens contains the key components of a circadian clock, and time-of-day differences exist in the expression of GSH and GSH related enzymes involved in maintaining GSH homeostasis. GSH levels in the rat lens were highest at the start of night which represents the active phase of the rat when high GSH levels may be required to counteract oxidative stress induced by cellular metabolism. Future work to directly link the clock to regulation of GSH levels in the lens will be important in determining whether the clock can be used to help restore GSH levels in the lens.